PUBLIC RELATIONS AND NEW MEDIA AT FAITH-BASED HEALTH INSTITUTION - Kholifatul Fauziah (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to elaborate on the use of new media in the public relations of faith-based health institutions during the pandemic. Besides, this research is aimed at exploring the audience engagement from it. This research was conducted considering that theoretically, enrichment is needed to map how public relations in faith-based health institutions interact through new media to bridge the relationship between institutions and stakeholders, preach the faith mission, and develop a positive reputation for the institution. In practical terms, the study in the field is crucial to becoming lessons learned for policymakers at related institutions. This research took a case study at the PKU Muhammaidyah Hospital of Yogyakarta City. The institution was chosen because it represents a health institution under the official auspices of one of the most prominent faith-based organizations in the world, Muhammadiyah, and uses new media intensively to communicate with stakeholders during the pandemic. This type of research is mixed-method research with a qualitative approach using percentage statistical data. Data collection techniques used are documentation through the Instagram contents of PKU Muhammadiyah of Yogyakarta City. The findings show that the use of Instagram by PKU Muhammadiyah Hospital in Yogyakarta City has reflected a weighting that is in accordance with the character of the organization as a faith-based health institution. Audience effect conversions are dominated by product branding content. The discourse raised in the communication process through new media in this study is how to combine religious messages with product and corporate branding.